Formulation of a Typical Development Strategy for Agricultural Enterprises (by the method of Hoshin Kanri) - IRYNA BORYSHKEVYCH (Vasyl Stefanyk Precarpathian National University, 2019)
Modern conditions of business globalization, considerable limitation of resources, strengthening competition and acceleration of technological innovations demand from the agricultural enterprises' ability to adapt quickly to changing conditions of the external environment. The key to their successful product development is to ensure the most effective use of the available resource potential. In science and practice, there is a large variety of methodological tools that contribute to improving the functioning of economic entities. One such tool that ensures the achievement of effective development, forming a sustainable competitive advantage is a strategy. We are talking about a complex model that covers all processes in the enterprise. The use of advanced methods of strategy development by managers of agricultural enterprises is the key to its successful effective implementation and increase the competitive advantages of the enterprise in the market environment. The article analyzes the existing methods of strategic planning which are based on various methodologies of building strategies. The following methods are characterized: resource method, target method, extrapolation method, interpolation method, statistical testing method, criterion method, normative method, balance method, matrix method and strategic plan construction. The Hoshin Kanri method based on the application of the Deming cycle and representing the concept of cyclic control is investigated based on the studied sources. A typical strategy for the development of an agricultural enterprise in the form of an X-matrix has been developed. This strategy is designed for 3 years and includes strategic and tactical goals, processes and results, between which appropriate correlations are established. Among the strategic goals that are typical for agricultural enterprises, the following are highlighted: improving business efficiency, increasing the efficiency of sales activities, introducing innovative technologies into production and optimizing business processes. Accordingly, the management of agricultural enterprises can form a greater number of promising goals, based on the needs of economic entities. The obtained results form the basis for further studies of the mechanism of the development strategy formation and implementation in the agricultural enterprises.